2023
DOI: 10.1039/d3ea00046j
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the octanol–air partitioning ratio: a critical review

Abstract: The octanol-air partition ratio KOA, also referred to as the octanol-air partition coefficient, has a wide range of applications in environmental chemistry. In this review, we explore the historical context...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 174 publications
0
4
0
Order By: Relevance
“…The fugacity framework is used because comparison between fugacities within a model directly describes the direction of chemical flux within a system and can be effectively modeled with only the octanol-air partitioning ratio, K oa , allowing the model to work independently of chemical identity . The use of K oa aligns with previous modeling techniques in the indoor environment, ,,, and is preferred due to the widespread availability of K oa values for compounds in the literature and because partitioning to a wide range of compartments (i.e., the surfaces, particles, and bulk phase, see Table S1) and diffusivity in the bulk phase can be empirically described with the K oa . While other parameters to describe compound partitioning behavior are available, K oa allows broad comparisons to be drawn across compound classes and is, therefore, a practical choice for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The fugacity framework is used because comparison between fugacities within a model directly describes the direction of chemical flux within a system and can be effectively modeled with only the octanol-air partitioning ratio, K oa , allowing the model to work independently of chemical identity . The use of K oa aligns with previous modeling techniques in the indoor environment, ,,, and is preferred due to the widespread availability of K oa values for compounds in the literature and because partitioning to a wide range of compartments (i.e., the surfaces, particles, and bulk phase, see Table S1) and diffusivity in the bulk phase can be empirically described with the K oa . While other parameters to describe compound partitioning behavior are available, K oa allows broad comparisons to be drawn across compound classes and is, therefore, a practical choice for this study.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that they may differ largely in the octanol-air partition coefficient (K oa ) and gaseous−particle phase distributions, as well as the potency for long−distance transport. 37 As for most of the NPPs only predicted K oa values are available which may offer uncertain results for some SVOCs, 38 better assessment or measurement of K oa and gas-particle dispersion coefficient is required to understand their behavior in atmospheric environment. 39 Therefore, following our study which revealed the broad occurrences of selected NPPs in PM 2.5 from different cities, further studies are needed to better elucidate their chemical-specific gas−particle distributions and atmospheric transport.…”
Section: Chemicals and Reagents Reference Standards Of 24mentioning
confidence: 99%
“…The above hypothesis is illustrated by the following adjustment of the mathematical model in the literature29, which provided the expressions for the mass addition due to the SVOC adsorption. The adjustments involved a change in the expressions of the octanol partition coe cients VI,37 , from constant values to (i) being dependent on the time since the exposure start, and the RH in the Aula (Equations 1 to 3), and (ii) an example of a potential SVOC emission episode (Equation 4). As the gas-phase concentrations of the sorbing SVOCs depend on the partition coe cients, these then also changed over time in the adjusted model.…”
Section: Mathematical Modelling and Ttingmentioning
confidence: 99%